2020
DOI: 10.1177/0972753121998470
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders in Individuals With High Risk for Diabetes in Indian Population

Abstract: Background: Sleep restores physiology and neurochemical components of our body and is essential for physical and mental health. Sleep disorders (SDs) are associated with insulin resistance and metabolic disorders. The association between SDs and diabetes needs to be understood in the Indian population. Purpose: The purpose was to investigate the association between SD and diabetes in the Indian population. Methods: As a part of nationwide Niyantrita Madhumeha Bharata Abhiyaan-2017 (NMB-2017), a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Stressful conditions that reduce sleep quality or duration, or both, can reduce insulin sensitivity and glucose tolerance, leading to development of type 2 DM. Maity et al, (2020) The study also showed that difficulty maintaining sleep (OR=3.50; 95% CI=1.30-9.45) and waking up too early in the morning (OR=2.69; 95% CI=1.21 -5.98) experienced up to five times a month significantly increases the risk of prediabetes (Engeda et al, 2013).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Stressful conditions that reduce sleep quality or duration, or both, can reduce insulin sensitivity and glucose tolerance, leading to development of type 2 DM. Maity et al, (2020) The study also showed that difficulty maintaining sleep (OR=3.50; 95% CI=1.30-9.45) and waking up too early in the morning (OR=2.69; 95% CI=1.21 -5.98) experienced up to five times a month significantly increases the risk of prediabetes (Engeda et al, 2013).…”
Section: Discussionmentioning
confidence: 87%
“…Prolonging sleep latency also had a significant effect on increasing the risk of type 2 DM (OR=1.085; 95% CI=1.008-1.168; p=0.010) (Maity et al, 2020). A prospective cohort study conducted on 241,949 adults in Australia found that a sleep duration of less than 6 hours significantly increased the risk of type 2 DM compared with a sleep duration of 7 hours per night even after excluding confounding factors (HR=1.29; 95% CI =1.08-1.53; p=0.004).…”
Section: Discussionmentioning
confidence: 97%
“…Disruptions to this essential biological need can significantly impact various aspects of health [ 45 , 46 , 47 ]. Recent epidemiological studies have revealed that sleep deprivation can lead to physiological changes that increase the risk of chronic diseases [ 41 , 42 , 43 ], including hypertension [ 41 , 44 , 48 ] (HT), coronary heart disease [ 48 , 49 , 50 , 51 , 52 ] (CHD), and diabetes mellitus (DM) [ 53 , 54 , 55 , 56 ]. Meeting optimal levels of sleep was proven to have survival benefits and reduce the risk of all-cause mortality while, in turn, providing a better quality of life [ 43 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life depends on several lifestyle habits which can increase the risk of diabetes. Studies showed that inadequate sleep and worse sleep quality increase the risk of diabetes (11). As diabetes is a metabolic disorder our diet pattern plays an important role in diabetes.…”
Section: Introductionmentioning
confidence: 99%